Prescription patterns of psychotropics in patients receiving synthetic glucocorticoids. (2nd August 2020) - Yatomi, T.; Uchida, T.; Takeuchi, H.; Kuramochi, S.; Yoshimura, K.; Mimura, M.; Uchida, H.
Abstract : Objective: Synthetic glucocorticoids cause various psychiatric symptoms. Prescription of psychotropic drugs could be considered to be a proxy for manifestation of psychiatric symptoms. The aim of this study was to investigate the prescriptions of psychotropics in outpatients receiving synthetic glucocorticoids. Methods: We used the claims sampling data during January 2015 from the National Database of Health Insurance Claims and Specific Health Checkups of Japan made by the Ministry of Health, Labor, and Welfare in Japan. We compared the prescription rates of psychotropics between outpatients receiving oral synthetic glucocorticoids and age‐ and sex‐matched controls and the prescription rates of psychotropics among the eight dosage groups of synthetic glucocorticoids by chi‐squared test, and chlorpromazine/imipramine/diazepam equivalent doses (or daily defined doses) of respective psychotropics among these groups using Welch's t ‐test. Results: Synthetic glucocorticoids were prescribed to 3.1% ( n  = 18 122) of 581 990 patients. The prescription rates of psychotropics were significantly higher among the synthetic glucocorticoid recipients than among the non‐recipients: antipsychotics, 1.8% ( n  = 321) vs. 1.1% ( n  = 201) ( P  = 1.4 × 10 −7 ); antidepressants, 4.0% ( n  = 724) vs. 2.0% ( n  = 359) ( P  = 8.7 × 10 −30 ); anxiolytics/hypnotics, 16.7% ( n  = 3029) vs. 10.2% ( n  = 1841) ( P  = 2.7 × 10 −75 ); and mood stabilizers, 1.3% ( n  = 238) vs. 0.7% ( n  = 120) ( P  = 3.6 × 10 −10 ) respectively. There was no significant difference in the prescription rates of any psychotropic drugs, other than anxiolytics/hypnotics, among the eight synthetic glucocorticoid dosage groups. Conclusion: Prescriptions of oral synthetic glucocorticoids were found to be associated with the use of any of the types of psychotropic drugs, other than anxiolytics/hypnotics, although a causal relationship could not be confirmed due to the retrospective and cross‐sectional nature of this study.